Democracy betrayed : the Wilmington race riot of 1898 and its legacy - Cecelski, David S.; Tyson, Timothy B.; Franklin, John Hope, 1915-2009 (The University of North Carolina Press, 1998)
Democracy Betrayed: The Wilmington Race Riot of 1898 and Its Legacy.